2002
DOI: 10.1111/j.1745-3984.2002.tb01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Examinees Use Judgments of Item Difficulty to Improve Proficiency Estimates on Computerized Adaptive Vocabulary Tests?

Abstract: Recent simulation studies indicate that there are occasions when examinees can use judgments of relative item difficulty to obtain positively biased proficiency estimates on computerized adaptive tests (CATs) that permit item review and answer change. Our purpose in the study reported here was to evaluate examinees' success in using these strategies while taking CATs in a live testing setting. We taught examinees two item difficulty judgment strategies designed to increase proficiency estimates. Examinees who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 17 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…Despite these restrictions, means across conditions ranged from 7.32 (KS, KSA) to 7.88 (GKS) and showed no statistically significant differences overall ( F (6, 211) = 1.90, p = .10) with 92.6% of the participants providing ratings of either 7 or 8. These high levels of perceived adequacy of review opportunities within restricted review CAT conditions replicate findings from Vispoel et al (2000, 2002), and demonstrate once again that restricted review is viewed very favorably by most examinees.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite these restrictions, means across conditions ranged from 7.32 (KS, KSA) to 7.88 (GKS) and showed no statistically significant differences overall ( F (6, 211) = 1.90, p = .10) with 92.6% of the participants providing ratings of either 7 or 8. These high levels of perceived adequacy of review opportunities within restricted review CAT conditions replicate findings from Vispoel et al (2000, 2002), and demonstrate once again that restricted review is viewed very favorably by most examinees.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Despite the general pattern of detrimental results from using the K and GK strategies, Vispoel et al (2002) still found that a few examinees in the K and GK conditions benefited from using those strategies. Not surprisingly, these examinees performed well in judging item difficulties and usually changed answers when the computer algorithm operated consistently.…”
Section: Research On Changing Answers To Cat Items Using Judgments Ofmentioning
confidence: 99%
See 3 more Smart Citations